Development of a lock biometric authentication system for a battery powered locking device - Ismail, Iman Fitri; Mas Fawzi, Mas Fawzi; Wan Jamaludin, Wan Akashah; Madon, Rais Hanizam; Abdullah, Ahmad Fauzan; Abdullah, Mohamad Ashik (Penerbit UTHM, 2021)
This paper describes the development of a biometric authentication system in a battery-powered locking device. It differs from the conventional locking system, which connected to an external power supply. The system focuses on a fingerprint-based identification with single button operation. A fingerprint sensor readily available in the market was integrated with an Arduino as the processing unit to unify the button operation as means to trigger functions on the fingerprint sensor and actuator motors, as well as indicating lights for user feedback. The aim of the seamless fingerprint authentication requires a brief matching of users’ fingerprints. A prototype of the system was built and tested. It was found that the device is able to match a fingerprint in less than 1s for up to 50 registered fingerprints. Using a nominal battery capacity of the 12V lithium battery pack with 5000mAh, the amount of current supply to the actuator is sufficient for 400 activations.